Fifty Years of Advances in Neuroendocrinology. (November 2018) - Russell, John A.
Importance of the neuroendocrine brain for health and happiness has become clear since the 1960s. Foundations laid 100 years ago culminated in Geoffrey W Harris's model of control by the brain of secretion of anterior and posterior pituitary gland hormones through, respectively, releasing factors secreted into the hypothalamic-hypophysial portal system, and directly from axon terminals into the systemic circulation. Confirmation, expansion and deepening of knowledge and understanding have followed increasingly sophisticated technology. This allowed chemical characterisation of the posterior pituitary hormones, oxytocin and vasopressin, the releasing factors, their receptors and genes, location of the neurosecretory neurons in the hypothalamus, and how their activity is controlled, including by neural and hormonal feedback, and how hormone rhythms are generated. Wider roles of these neurons and their peptides in the brain are now recognised: in reproductive and social behaviours, emotions and appetite. Plasticity and epigenetic programming of neuroendocrine systems have emerged as important features.